EXPLORING THE IMPACT OF PAYLATER PAYMENTS ON CONSUMER BEHAVIOR AND PUBLIC FINANCIAL MANAGEMENT: A SYSTEMATIC LITERATURE REVIEW - Anggorowati, Luki Sri (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
The development of financial technology has driven the emergence of various innovations in payment systems, one of which is the paylater service or